Cotton genetic diversity study by AFLP markers - Murtaza, Naveed (Electronic Journal of Biotechnology, 2006)
Amplified fragmentlength polymorphism (AFLP) markers have been used to ascertain the intensity of inherent diversity and relatedness in cotton (Gossypium spp.) plants. The effectiveness of this method to distinguish inter and intra specific difference in cotton could be handy in cultivar recognition and in marker assisted parental selection tool for plant breeders. Twenty cotton cultivars belonging to Gossypium hirsutum L., and G. arborium L. from the Pakistan and US origin were used for AFLP based genetic diversity estimates. The objective of this study was to assess the level of genetic variation among some cotton cultivars belonging to the old and new world species of cotton. Four EcoRI-MseI primer-pair combinations were used forthe AFLP analysis. The AFLP data assigned the genotypes into groups that corresponded with their origin and lineage relationships and showed a narrow genetic base among these cultivars.